PENDIDIK DALAM PERSPEKTIF PENDIDIKAN ISLAM - Siti Suwaibatul Aslamiyah (Al Hikmah: Jurnal Studi Keislaman, 2013)
Educationis amajor factor inthe success ofeducation. Its presencein the learning processis very importantandcan not bereplaced bythe mostmoderntechnologythough,becauseonly througheducator/teacherhumanelementssuchidealscan be achieved.In an articleentitled "Education in the perspectiveof Islamic Education" wastryingto explainabout thingsrelated to theeducators/teachers, namely: understandingeducator, conditions that must beheld byeducators, qualities that should beeducators, duties, responsibilities and rightseducators, andeducatorsvirtue.As aconclusionof this discussionis thatas an educator/teacherought tohavesome terms andsomequalities that should beandhas dutiesand responsibilitiesarequite heavybutverypreciouswith AllahSWT. And because ofits duties and responsibilities, then an educatorhas the rightto earn a salaryand awards. Foreducators/teachers orpeopleknowledgeableandwilling topractice itGod willraise their statusandhonor. So it is withthe angels, the inhabitants of the heavensand the earthare allprayingto thesamepeople who areknowledgeableandapply their knowledgeso that theyget thesafety andhappiness. But forthose who areknowledgeablebutconcealtheir knowledgeAllah willcurbwithfetters ofhell fire. Similarlywhen thesinnersinsare heavierthanthe sin oftheignorant, andbearthe sins ofthose whofollow it.